2011
DOI: 10.1002/cncr.26452
|View full text |Cite
|
Sign up to set email alerts
|

Clinical behavior and treatment outcome of primary nasal diffuse large B‐cell lymphoma

Abstract: BACKGROUND: Nasal diffuse large B-cell lymphoma (DLBCL) is rare. The objective of this study was to evaluate the clinical features and treatment outcomes of patients with nasal DLBCL. METHODS: Twenty-five patients were included in the study. All patients received combination chemotherapy with or without radiotherapy. RESULTS: Patients with nasal DLBCL usually were older and were predominantly men with early stage disease, low frequency of B symptoms and elevated lactate dehydrogenase (LDH), good performance st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
1
13
0
3
Order By: Relevance
“…Nevertheless, the true prognosis of patients with SN-DLBCL remains controversial, as does how to achieve the best treatment outcomes after the introduction of R, due to the rarity of the disease and the heterogeneity of current treatment options regarding the incorporation of IFRT. Lu et al reported that the 3-year OS rate in 25 patients with nasal DLBCL was only 44%, although these patients predominantly had early-stage disease, low-risk IPI and high response rates [15]. However, other studies have suggested a more favorable prognosis for patients with…”
Section: Patient Characteristicsmentioning
confidence: 97%
“…Nevertheless, the true prognosis of patients with SN-DLBCL remains controversial, as does how to achieve the best treatment outcomes after the introduction of R, due to the rarity of the disease and the heterogeneity of current treatment options regarding the incorporation of IFRT. Lu et al reported that the 3-year OS rate in 25 patients with nasal DLBCL was only 44%, although these patients predominantly had early-stage disease, low-risk IPI and high response rates [15]. However, other studies have suggested a more favorable prognosis for patients with…”
Section: Patient Characteristicsmentioning
confidence: 97%
“…Monoklonal anti CD-20 antikoru rituksimabın kullanımıyla sağkalım oranları artmıştır. 7 Italiano ve ark. 80 yaş üzeri hastalarda düşük doz CHOP kemoterapi protokolüne ek olarak verdikleri rituksimab tedavisi sonucunda 2 yıl üzeri sağ kalımı %60 olarak göstermişlerdir.…”
Section: Olgu Sunumuunclassified
“…A histologia maiormente encontrada é de carácter não epitelial primário. Muitos dos pacientes em séries revisadas têm tido diagnóstico 1 …”
Section: Introductionunclassified
“…La afección de las fosas nasales está descrita entre el 1.5% -5%, se encuentra mayormente en pacientes entre la octava y novena décadas de la vida, y en más proporción en pacientes de raza asiática 1,2 . Si bien, en esta raza son más comunes los linfomas en el área nasal, en poblaciones occidentales también es descrita, con una variación histológica respecto a su presentación y el linfoma no Hodgkin con población de células B es el más frecuente en poblaciones occidentales, mientras en Perú y Asia se describe una prevalencia mayor de linfomas no Hodgkin con células T 3,4 .…”
Section: Introductionunclassified